What Factors Encourage Young People to Engage in Substance Use? Substance Use and Associated Factors Among Youth in Southwest Ethiopia: A Community-Based Study - Geleta, Tinsae Abeya; Deriba, Berhanu Senbeta; Dirirsa, Dejene Edosa (Frontiers in Public Health, 2022)
Background Substance use indicated the use of psychoactive substances such as alcohol, cigarettes, khat, and illegal drugs. Substance use has varying impacts on the health and socio-economics of countries, and is a major public health concern globally. Currently, substance use is a common public health problem among Ethiopian youth mainly in the city of Jimma. Therefore, this study aimed to assess the magnitude of Cigarette smoking, alcohol drinking, khat chewing, and associated factors among the youth of Jimma town in 2019. Methods A community-based cross-sectional study was conducted among youth of Jimma town from March 2019 to April 2019. A simple random sampling technique was used to select 423 study participants. Data were collected using a structured interviewer-administered questionnaire. The collected data were entered into EPI data manager version 4.4.1 and transported to SPSS version 23 for data cleaning and analyses. The disruptive study was carried out to determine the prevalence of cigarette smoking, alcohol consumption, and khat chewing. Binary and multivariable analyses were carried out to identify factories associated with cigarette smoking, alcohol consumption, and khat chewing. Finally, adjusted odds ratios (AOR) with 95% confidence intervals (CI) were used to determine the presence and strength of association. Results The current prevalence of cigarette use, alcohol use, and khat use was 16.0, 30.6, and 45.7%, respectively. Factors associated with current smoking use were substance use by siblings, subjective norm factors, and perceived benefits of substance use. Factors associated with current alcohol consumption were youth who highly perceived substance use as important. Factors associated with current khat use were male, substance use by siblings, out-of-school youth, and subjective norms. Concussion The study findings indicated that the prevalence of khat, alcohol, and cigarettes was high among the youth of the city of Jimma. To reduce the prevalence of khat, alcohol, and cigarettes among youth, coordinated efforts from the youth, the government, health professionals, and the community at large are needed.